Empowering Sidomekar Village Community through orange peel-based body scrub production training - Boy Arief Fachri; Bekti Palupi; Meta Fitri Rizkiana; Istiqomah Rahmawati; Devi Prayuga; Achmad Rodi Soleh; Icha Shofia Dihasti; Hosshofil Azhar Azizi; Lalu Dimas Putra Hermanto; Nabilla Widya Rahman; Ahmad Reza Maulufi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
One of the villages that already has a Memorandum of Understanding (MoU) as a fostered village of Jember University is Sidomekar Village located in Semboro District, Jember Regency, East Java. The problem of Sidomekar Village that is highlighted is the low selling price of Semboro oranges during the harvest season, sometimes only Rp2000 per kg, thus negatively impacting farmers' income. The solution to this problem is to utilize orange peel waste as an active ingredient in body scrub preparations so that it can be used as one of the village's superior products. This community service program aims to provide solutions to the problems faced by partners while increasing the Village Development Index, especially in terms of the Economic Resilience Index through the development of superior village products based on orange peel waste. This service program was carried out by providing socialization attended by 35 participants regarding the process of making and using tools to produce body scrubs from orange peels. The increase in knowledge and skills of participants increased by 90% based on the active participation in the socialization event during the question and answer session and practice of making body scrubs from orange peels.